PENERAPAN METODE BERCERITA UNTUK MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN DI TK BHAYANGKARI MEMPAWAH HILIR - Dwi Putri Noviani; Muhamad Ali; Desni Yuniarni (Universitas Tanjungpura, 2019)
AbstractThis research is motivated by the existence of children's language skills that are not yet developed as they should be in accordance with the realm of their development. This makes the researchers want to know how the teachers do to develop the language skills of children at TK Kemala Bhayangkari 2. The general objective in this study was to determine the effect of the method of storytelling on the development of language skills of children at TK Kemala Bhayangkari 2. This research uses descriptive method and qualitative approach. Data obtained in the form of words and images. The data source consisted of 1 teacher in class A and 17 children as research subjects. After the data is collected, the data is presented and a conclusion is drawn. From the results of the study it was found that the application of the method of storytelling to develop children's language skills is very influential in children's language development in TK Kemala Bhayangkari 2 which can be seen from significant developments that develop very well. Teachers are expected to pay more attention and add more creative ideas when telling stories, so that each child is able to develop optimally. The need for Bhayangkari kindergarten to provide support in the form of facilitating or reproducing story books and media that can help develop aspects of children's language. Keywords: Application of Storytelling Method, Children's Language Ability